Anthroponymic materials of the Southern Iberian Peninsula in ancient times (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This article studies the personal names attested in the south of the Iberian Peninsula and, by means of some common features, proposes the existence of a southern anthroponymic landscape in the area of Guadalquivir.
Keywords: Onomastics; Hispanic personal names; southern Hispania; Turdetanian; Tartesian; Baetica